CT findings in viral lower respiratory tract infections caused by parainfluenza virus, influenza virus and respiratory syncytial virus. Issue 26 (June 2016) - Kim, Min-Chul; Kim, Mi Young; Lee, Hyun Joo; Lee, Sang-Oh; Choi, Sang-Ho; Kim, Yang Soo; Woo, Jun Hee; Kim, Sung-Han
Abstract : Abstract: Viral lower respiratory tract infections (LRTIs) can present with a variety of computed tomography (CT) findings. However, identifying the contribution of a particular virus to CT findings is challenging due to concomitant infections and the limited data on the CT findings in viral LRTIs. We therefore investigate the CT findings in different pure viral LRTIs. All patients who underwent bronchoalveolar lavage (BAL) and were diagnosed with LRTIs caused by parainfluenza virus (PIV), influenza virus, or respiratory syncytial virus (RSV) between 1998 and 2014 were enrolled in a tertiary hospital in Seoul, South Korea. A pure viral LRTI was defined as a positive viral culture from BAL without any positive evidence from respiratory or blood cultures, or from polymerase chain reaction (PCR), or from serologic tests for bacteria, fungi, mycobacteria, or other viruses. CT images of 40 patients with viral LRTIs were analyzed: 14 with PIV, 14 with influenza virus, and 12 with RSV. Patch consolidation (≥1 cm or more than 1 segmental level) was found only in PIV (29%) ( P = 0.03), by which CT findings caused by PIV could resemble those seen in bacterial LRTIs. Ground-glass opacities were seen in all cases of influenza virus and were more frequent than in PIV (71%) and RSV (67%) ( P = 0.05). Bronchial wall thickening was more common in influenza virus (71%) and RSV (67%) LRTIs than PIV LRTIs (21%) ( P = 0.02). With respect to anatomical distribution, PIV infections generally affected the lower lobes (69%), while influenza virus mostly caused diffuse changes throughout the lungs (57%), and RSV frequently formed localized patterns in the upper and mid lobes (44%). The CT findings in LRTIs of PIV, influenza virus, and RSV can be distinguished by certain characteristics. These differences could be useful for early differentiation of these viral LRTIs, and empirical use of appropriate antiviral agents.